Lionfish (Pterois volitans) do not show directional preferences for ambient underwater soundscapes during diurnal hours - Roxanne B Holmes; Nadia M. Hamilton; Stephen D. Simpson; James E. Herbert-Read (Marine Biology, 2025)
Sound is a valuable cue in the marine environment that can inform animals about habitat location and community composition. Indeed, sound is often used for orientation and navigation by larval reef fishes during settlement. However, despite sound’s role in the early life of reef fishes, whether post-settlement reef fishes use ambient soundscapes to inform their movement decisions remains less clear. In an in-situ playback experiment in Curaçao, the Dutch Caribbean, settled individuals of an invasive predator, the Indo-Pacific lionfish ( Pterois volitans ), showed no preference to move towards the playbacks of two different habitat types during daylight hours. In particular, lionfish did not prefer to move towards the sounds of sandy or reef habitat playbacks when tested against a silent control. Moreover, when given a choice between simultaneous sandy and reef habitat playbacks, lionfish showed no preference for the soundscape of either habitat type. While the activity of lionfish was strongly correlated with their body size, with larger fish being more active, activity was not affected by habitat playback, nor did body size affect their preference for the soundscapes of either habitat type. While acoustic lures have been speculated to be a promising addition to existing lionfish trap designs, daytime playbacks of ambient soundscapes are unlikely to be successful in attracting lionfish post-settlement, ultimately affecting their efficacy.